EVALUASI PEMBELAJARAN PAI DAN IMPLIKASINYA TERHADAP MOTIVASI BELAJAR DI MTS NURUL HASAN SUMBERAGUNG NGRAHO BOJONEGORO - Mochamad Hariyadi; Ulfa (STKIP Subang, 2026)
Learning evaluation is an important component in determining the success of the educational process, particularly in Islamic Religious Education (PAI). This study aims to analyze the implementation of PAI learning evaluation and its implications for students' learning motivation at MTs Nurul Hasan Sumberagung, Ngraho, Bojonegoro. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving school principals, PAI teachers, and students. The findings indicate that PAI learning evaluation was conducted through formative and summative assessments covering cognitive, affective, and psychomotor domains. Evaluation activities included written tests, assignments, observations, and worship practices. The implementation of evaluation positively affected students' learning motivation by encouraging responsibility, learning discipline, participation, and enthusiasm in learning activities. However, several obstacles were identified, such as students' anxiety toward examinations and limited variation in assessment techniques. Therefore, innovative, objective, and comprehensive evaluation strategies are needed to improve students' motivation and learning outcomes.